Saponin Content of Sapindus rarak Pericarp Affected by Particle Size and Type of Solvent, its Biological Activity on Eimeria tenella Oocysts - Pasaribu , T.; Wina, E.; Sumiati,; Setiyono, A. (International Journal of Poultry Science, 2014)
Sapindus rarak is a species of soapberry and in Indonesia the trunks commonly used as board cast, match sticks and wooden crafts and the saponin containing fruits are used as a detergent for traditional clothes (called batik). Saponin has biological activity to damage protozoa. The study has been carried out to investigate the effects of particle size and type solvent on the concentration of saponin extracted from the Sapindus rarak pericarp powder (SRP) and to evaluate the activity of SRP on oocysts of Eimeria tenella in vitro. Completely randomized design with 2 factors was arranged to analyze saponin content. First factor was type of solvent, i.e., 70% methanol and water. Second factor was particle sizes of SRP, i.e., 75, 300 and 600 μm and the saponin analyses of each treatment was done in triplicates. Determination of total saponin as described by Hiai and Nakajima and total sapogenin according to Hiai method with some modification. In vitro assay was performed at several concentrations of SRP in water (100-0.01 mg/mL). Results showed SRP with 75 μm particle size showed the highest foam height and the highest total saponin content compared to those having 300 and 600 μm of particle size. Solvent and particle size significantly affected saponin content. Saponin content of SRP was higher when it was extracted with 70% methanol (35.98%) than extracted using water (32.53%). SRP with 75 μm particle size had higher saponin content (43.52%) than those with 300 and 600 μm particle size (37.54 and 21.71%). Sapogenin content extracted with 70% methanol and water was not significantly different (30.55 and 30.36%), but particle size affected the sapogenin content. At 75 μm particle size, the sapogenin content was significantly higher (35.51%) than 300 and 600 μm particle size (33.46 and 22.40%). The SRP with concentration of 100-1 mg/mL water inhibited sporulation of E. tenella oocysts more than 90%. It is proved SRP has the ability to destroy the development of Eimeria tenella.